"How did humans become resources anyway?:" HRD and the politics of learning the workplace - Fred M. Schied (Adult Education Research Conference, 1995)
This paper examines the origins of HRD. It argues that HRD emerged out of the struggles over the control of work and the workplace during and immediately after World War II.